PENGEMBANGAN VIDEO TUTORIAL BEBASIS JAGAT KERTI DAN FUN LEARNING UNTUK MOTORIK HALUS DAN KARAKTER ANAK USIA DINI - Putu Gede Surya Cipta Nugraha; I Nyoman Agus Suarya Putra; Ni Wayan Wardani (Jurnal Manajemen dan Teknologi Informasi, 2025)
Digital technology in classroom learning can enhance teachers’ instructional resources by providing access to diverse verbal and nonverbal presentation modes. In early childhood education, developing fine motor skills often presents a significant challenge. This study explores the effectiveness of video tutorials as visual communication media, integrating the Balinese cultural concept of Jagat Kerti (a principle of universal harmony) and an engaging learning approach to develop fine motor skills and promote character development in young children. The video activities involve shaping objects with plasticine and narrating the folk tale The Monkey and the Turtle. The media production process is divided into three stages: pre-production, production, and post-production. Observations showed that before watching the video, children could recognize shapes and colors but struggled to manipulate plasticine. After watching the video and receiving teacher guidance, the children successfully formed objects like apples and turtles and understood the story’s moral messages. Testing with a small group of young learners confirmed that this educational media is highly suitable as a learning tool for early childhood education.